ORGANIZATIONAL AND ECONOMIC MECHANISM OF INVESTMENT CONTROL AT MOTOR TRANSPORT ENTERPRISES - RYABOSHTAN, Liudmyla (Herald of Khmelnytskyi National University. Economic sciences, 2024)
In modern realities, the operation of motor transport enterprises in Ukraine has undergone significant complications due to globalization processes, instability in world markets, as well as in connection with the introduction of martial law in the country. In the conditions of these challenges, the main task for companies is to maintain competitive positions and stable functioning. This requires enterprises to quickly adapt to changes, to constantly respond to external threats in the business environment, as well as to preserve and strengthen their competitive advantages in the market. Investment controlling methods are a way of studying, measuring and summarizing the impact of various factors on changing the results of investment activity with the aim of improving it. The organizational and economic mechanism of investment controlling at the motor vehicle enterprise is based on a systemic approach that combines two main components: organizational and economic, which is important for ensuring the effectiveness of management of investment processes, as it allows for the integration of various aspects of management and control into a single system. The mechanism is a set of organizational, economic, social and informational forms of interaction of the participants of the investment process, which provides a comprehensive approach to the management of investments at the motor vehicle enterprise, which allows creating an effective controlling system that takes into account not only financial aspects, but also social and informational factors, which affect investment activity. The organizational and economic mechanism of investment controlling of motor vehicle enterprises is a complex system of management, economic and analytical tools that ensures effective coordination, monitoring, analysis and adaptation of investment processes at motor vehicle enterprises in order to increase their profitability, innovative development and competitiveness.